PENINGKATAN AKTIVITAS SITOTOKSIK DOXORUBICIN TERHADAP SEL HeLa, SEL WiDr, SEL MCF-7, DAN SEL MCF-7/DOX OLEH KALIUM PGV-0 DAN PENELUSURAN MEKANISME MOLEKULER PADA PROTEIN KINASE IN SILICO - , NUR ISMIYATI, Dr. Ratna Asmah Susidarti, M.Si., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Cancer is a disease that causes high mortality in the world. Discovery and development of co-chemotherapeutic agent continue to increase chemotherapeutic agentâs effectiveness and decrease its side effect. Curcumin can inhibit the growth of several cancer cell lines by various mechanisms, one of them is by disrupting the signal transduction of MAP kinase pathways. Curcumin analogues, PGV-0, also has potential cytotoxic activity on some cancer cell lines better than curcumin. However, PGV-0 has a low solubility in water, so Kalium PGV-0 was synthesized. This study aims to determine K PGV-0 potential as a cochemotherapeutic agent targeting protein in MAP Kinase pathway, especially with the protein target EGFR, IKK, Pgp, and COX-2. Cytotoxic activity of K PGV-0 alone and in combination with doxorubicin was measuring using MTT assay on HeLa, WiDr, MCF-7, and MCF-7/dox cells. Molecular mechanisms that mediates cytotoxic activity of K PGV-0 was identified in silico through molecular docking by PLANTS software. K PGV-0 as ligand was prepared using Marvin Sketch, while protein targets were prepared using YASARA. K-PGV0 showed cytotoxic activity on HeLa, WiDr, MCF-7, and MCF- 7/dox with IC50 of 59, 49, 87, and 7 Î¼M respectively. The combination application of K-PGV0 and doxorubicin showed that K PGV-0 increase doxorubicin cytotoxicity. The molecular mechanism in silico showed K PGV-0 interactions to EGFR and Pgp on their ATP binding site with high affinity. K PGV-0 also inhibited of COX-2 protein, but its interaction to IKK protein was low. These result suggested that K PGV-0 is potentially to be developed as cochemotherapeutic agent, with molecular mechanism need to be explored.